2006
DOI: 10.53841/bpsecp.2006.23.4.80
|View full text |Cite
|
Sign up to set email alerts
|

Every team matters: The contribution educational psychology can make to effective teamwork

Abstract: Teamwork has never been more topical. This is evident not only in the practice of educational psychologists but also in the dominant discourse surrounding government policy. Multi-agency collaboration lies at the heart ofEvery Child Matters. The underlying assumption is that multi-agency teamwork is the best way to work, ensuring the most complete and effective service to children and their families. While not disputing this, we feel that the complexities of teamwork are not sufficiently considered. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…while Leadbetter (2006) looked into a four year research project into the developmental process a team goes through which was based on activity theory and concluded that a greater knowledge of what may be happening within teams, and the possible dynamics and underpinning psychological and social processes, should be helpful and should facilitate increased reflective practice (p57) Dennison, McBay and Shaldon (2006) reflected on the contribution educational psychology can make to effective teamwork. Adopting a psychodynamic, social constructionist and systemic background, they reflected on their experiences of working in multiagency teams and noted that psychological understanding of teams/groups and psychological input to the setting up and maintenance of those teams/groups played a crucial factor.…”
Section: 4mentioning
confidence: 99%
“…while Leadbetter (2006) looked into a four year research project into the developmental process a team goes through which was based on activity theory and concluded that a greater knowledge of what may be happening within teams, and the possible dynamics and underpinning psychological and social processes, should be helpful and should facilitate increased reflective practice (p57) Dennison, McBay and Shaldon (2006) reflected on the contribution educational psychology can make to effective teamwork. Adopting a psychodynamic, social constructionist and systemic background, they reflected on their experiences of working in multiagency teams and noted that psychological understanding of teams/groups and psychological input to the setting up and maintenance of those teams/groups played a crucial factor.…”
Section: 4mentioning
confidence: 99%